Localization of the ribosomal genes in Anguilliformes (Chordata, Osteichthyes) - COLUCCIA, ELISABETTA; CANNAS, RITA; SALVADORI, SUSANNA; MILIA A; DEIANA A. M (2001)
Localization of the ribosomal genes in Anguilliformes (Chordata, Osteichthyes) E. Coluccia, R. Cannas, A. Milia, A. M. Deiana, S. Salvadori Dipartimento di Biologia Animale ed Ecologia, Università di Cagliari, Viale Poetto 1, 09126 Cagliari, Italy Keywords: Anguilliformes, FISH, ribosomal genes Ribosomal genes are organized in two multiple tandemly-arrayed units: the major family encoding for 28S, 18S and 5.8S rRNA and localized in the nucleolar organizer region (NOR), and the minor family encoding for 5S rRNA. Their chromosomal localization represents useful markers for karyotype analysis and for the investigation of the phylogenetic relationships among related species, especially in fishes in which euchromatic structural banding patterns are difficult to obtain. In the present study, the chromosomal evolution of rDNA within the Anguilliformes order was studied through the mapping by FISH of the two ribosomal gene families in some species from different families, and by comparison with data on other Anguilliformes. 45S rDNA has been mapped in Gymnothorax unicolor (Muraenidae), Conger conger (Congridae), Ophisurus serpens and Echelus myrus (Ophichthidae); it was detected only in a chromosome pair in all species, as in the other previously studied Anguilliformes. This situation is the most frequent in teleosteans. A terminal localization on the short arm of a submetacentric and subtelocentric chromosome pair was found in O. serpens and C. conger respectively; this is the most frequent situation among Anguilliformes and fishes in general; an interstitial location on a acrocentric chromosome pair was detected for G. unicolor and E. myrus. NOR is positive to silver staining and CMA3 banding in all species in which these techniques have been applied. Between the two Mediterranean moray eels (Muraena helena and G. unicolor) a pericentric inversion involved the NOR bearing pair. The ribosomal gene families are located on separate chromosome pairs in Anguilla anguilla and A. rostrata 1, 2 and in most fishes. In the ...